Approaches to Strengthen Learning Community for Improvement in Learning Outcomes - Shahida, Naghma (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Learning Communities have huge potential in exchanging experiences and forming a collective knowledge on the basis of interaction among individuals. Learning communities are such environment where persons come together to obtain or share knowledge, to learn, to discuss and to be with other. A good learning community provides a conducive environment for teaching learning process and directly influences the learning outcomes. This qualitative study was conducted on a sample of 40 government secondary school principals selected from the Aligarh district of U.P. The researcher administered a self constructed structured Interview schedule based on 8 questions for data collection and the gathered information was analyzed through qualitative method. The analysis of the data gives interesting results regarding the various approaches like collaborative learning, respecting diversity, Standards-based curriculum, action plan in schools, fostering transformative approaches, provide equal importance to students, discussion among teachers and student and formal conferences which must be helpfulin strengthening learning communities.